Natural frequencies comparison between the pure granite and bonded granite-concrete - Arbain A.; Zawawi M.H.; Mohd Radzi M.R.; Hassan N.H.; Ahmad Mazlan A.Z. (American Institute of Physics Inc., 2023)
This paper presents the comparison between natural frequencies of pure granite and bonded granite-concrete. A granite is formed by natural processes and is naturally containing solid mass of minerals matter. On the other hand, concrete is not naturally formed but is a man-made material containing a mixture of natural granite, water, cement and other aggregates. In this research, the simulation setup and experimental procedure have been carried out for the purpose of finding the natural frequencies for both samples. For the simulation, a 3D shape of the sample has been modelled using SolidWork software based on the real sample before imported into ANSYS software for modal and harmonic response analyses. Whilst, for experimental, the geometry model of the real sample has been constructed in LMS Test Lab software and a rig to mount the sample has been developed before the Experimental Modal Analysis (EMA) is conducted. From the results, the natural frequency for the simulation in ANSYS software is determined at 7200 Hz, while for experimental, the natural frequency is at 7399.14 Hz. The percentage error between experiment and simulation is only 2.691 %, thus, it can be considered acceptable and the bonded granite-concrete can be used for the construction of the physical model. 2021 American Institute of Physics Inc.. All rights reserved.